Natural Occurrence of Enantiomers of Organic Compounds Versus Phytoremediations: Should Research on Phytoremediations Be Revisited? A Mini‐review. Issue 1 (19th November 2013) - Lojková, Lea; Vranová, Valerie; Rejšek, Klement; Formánek, Pavel
ABSTRACT Decontamination of polluted soils using plants is based on the ability of plant species (including transgenic plants) to enhance bioavailability of pollutants in the rhizosphere and support growth of pollutant‐degrading microorganisms via root exudation and plant species‐specific composition of the exudates. In this work, we review current knowledge of enantiomers of low‐molecular‐weight (LMW) organic compounds with emphasis on their use in phytoremediation. Many research studies have been performed to search for plants suitable for decontamination of polluted soils. Nevertheless, the natural occurrence of L‐ versus D‐enantiomers of dominant compounds of plant root exudates which play different roles in the complexation of heavy metals, chemoattraction, and support of pollutant‐degrading microorganisms were not included in these studies. D‐enantiomers of aliphatic organic acids and amino acids or L‐enantiomers of carbohydrates occur in high concentrations in root exudates of some plant species, especially under stress, and are less stimulatory for plants to extract heavy metals or for rhizosphere microflora to degrade pollutants compared with L‐enantiomers (organic acids and amino acids) or D‐carbohydrates. Determining the ratio of L‐ versus D‐enantiomers of organic compounds as a criterion of plant suitability for decontamination of polluted soils and development of other types of bioremediation technologies need to be subjects of future research. Chirality 26:1–20, 2013. © 2013 Wiley Periodicals, Inc.